Africa - An Unintended Collateral Victim of Russia – Ukraine War - Madziba, Nkobi (Southern African Journal of Security)
This paper examines security problems brought about by the Russian government in creating a war against Ukraine. The study emphasises Africa and other nations (which are either military aid donors or harbour companies and firms that produce and export military equipment) involved in the war for different reasons. Different scales at some point focus solely on Ukraine, with military aid could help donor countries involved in the war becoming limited, consequently leaving the Africa-a continent that relies heavily on aid faced with a serious security conundrum, especially in the wake of increasing terrorism-related activities not only in the continent but globally. The paper used secondary sources as the basis to conduct this research that as the war wages on, Africa becomes an unintended collateral victim of the Russia-Ukraine protracted war. The finding of the study is based on content analysis which shows that the war in Ukraine risks distracting or ‘taking away’ Russia and the West’s attention from Africa, resulting in the continent being vulnerable to combatting terrorism. Before divulging its main theme, which revolves around security challenges linked to the war. The paper used realism as its theoretical framework to discuss the protracted war between Russia and Ukraine, where issues such as why Russia is intransigently continuing with the war and why the West is interested in Ukraine. Realism is used as a basis for analysing the origin of the Russia-Ukraine war and not necessarily the impact of the war on Africa. It was established that realism is not used to justify Russia’s war in Ukraine but suggests that Russia’s behaviour is synonymous with the superpower.